Charged jet cross section and fragmentation in proton-proton collisions at √s=7TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Physical review, 2019)
We report the differential charged jet cross section and jet fragmentation distributions measured with the ALICE detector in proton-proton collisions at a center-of-mass energy √s=7 TeV. Jets with pseudorapidity |η|<0.5 are reconstructed from charged particles using the anti-kT jet-finding algorithm with a resolution parameter R=0.4. The jet cross section is measured in the transverse momentum interval 5≤pch jetT<100 GeV/c. Jet fragmentation is studied measuring the scaled transverse momentum spectra of the charged constituents of jets in four intervals of jet transverse momentum between 5 and 30 GeV/c. The measurements are compared to calculations from the pythia model as well as next-to-leading-order perturbative QCD calculations with powheg+pythia8. The charged jet cross section is well described by powheg for the entire measured range of pch jetT. For pch jetT>40 GeV/c, the pythia calculations also agree with the measured charged jet cross section. pythia6 simulations describe the fragmentation distributions to 15%. Larger discrepancies are observed for pythia8.
A Large Ion Collider Experiment Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Im Text steht s unter dem Wurzelsymbol
Gesehen am 24.10.2019